Reciprocal interference between the NRF2 and LPS signaling pathways on the immune‐metabolic phenotype of peritoneal macrophages - Federica Mornata; Giovanna Pepe; Chiara Sfogliarini; Electra Brunialti; Gianenrico Rovati; Massimo Locati; Adriana Maggi; Elisabetta Vegeto (Wiley, 2020)
Abstract The metabolic and immune adaptation to extracellular signals allows macrophages to carry out specialized functions involved in immune protection and tissue homeostasis. Nuclear factor erythroid 2‐related factor 2 (NRF2) is a transcription factor that coordinates cell redox and metabolic responses to stressors. However, the individual and concomitant activation of NRF2 and inflammatory pathways have been poorly investigated in isolated macrophages. We here took advantage of reporter mice for the transcriptional activities of NRF2 and nuclear factor‐kB (NFκB), a key transcription factor in inflammation, and observe a persisting reciprocal interference in the response of peritoneal macrophages to the respective activators, tert‐Butylhydroquinone (tBHQ) and lipopolysaccharide (LPS). When analyzed separately by gene expression studies, these pathways trigger macrophage‐specific metabolic and proliferative target genes that are associated with tBHQ‐induced pentose phosphate pathway (PPP) with no proliferative response, and with opposite effects observed with LPS. Importantly, the simultaneous administration of tBHQ + LPS alters the effects of each individual pathway in a target gene‐specific manner. In fact, this co‐treatment potentiates the effects of tBHQ on the antioxidant enzyme, HMOX1, and the antibacterial enzyme, IRG1, respectively; moreover, the combined treatment reduces tBHQ activity on the glycolytic enzymes, TALDO1 and TKT, and decreases LPS effects on the metabolic enzyme IDH1, the proliferation‐related proteins KI67 and PPAT, and the inflammatory cytokines IL‐1β, IL‐6, and TNFα. Altogether, our results show that the activation of NRF2 redirects the metabolic, immune, and proliferative response of peritoneal macrophages to inflammatory signals, with relevant consequences for the pharmacological treatment of diseases that are associated with unopposed inflammatory responses.